Ritual communication between Hindus and Muslims at sarasuta sacred place, in Lingsar Village West Lombok Regency - Sumada, I Ketut (International research journal of management, IT and social sciences, 2017)
This study intends to analyze ritual communication between two groups of people who have different religious in one sacred place. The problems associated with background meticulous ritual communication, the communication function of ritual, and the meaning of ritual communication between Hindus and Muslims at the sacred place of Sarasuta, in Lingsar village, West Lombok Regency. This research is a qualitative descriptive study. In this case, data are collected through observation, interview, and documentation. The analysis method is descriptive qualitative. Based on data collection and data analysis that background of ritual communication between Hindus and a number of Muslims at Sarasuta sacred place associated with the implementation of belief systems, execution culture, and the embodiment of social ties. Ritual communication functions associated with the cultural function, social function, aesthetic function, and religiosity function. The implied meaning concerning social meaning, ritual meaning, religious meaning, and ethics meaning.